Challenges in the Diagnosis and Treatment of Neuromyelitis Optica Spectrum Disorders: A Case Report With a Brief Review of Literature - Maria Elisa Morelli MD; Arianna Sartori MD; Antonio Bosco MD; Paolo Manganotti PhD, MD (SAGE Publishing, 2018)
Introduction . According to the 2015 diagnostic criteria for neuromyelitis optica spectrum disorders (NMOSD), in aquaporin-4 immunoglobulin G (AQP4-IgG) seronegative patients, NMOSD can be diagnosed if stringent clinical and magnetic resonance imaging (MRI) criteria are fulfilled; however, in these cases, diagnostic and therapeutic challenges could arise. Case Description . A young man presented a severe, bilateral optic neuritis and paraparesis in an acute phase. MRI evidenced 3 spinal cord T1-contrast-enhanced (T1-Gd+) myelitic lesions, extending <3 vertebral segments. AQP4-IgG and oligoclonal bands were negative. Following a relapse, MRI showed 2 T1-Gd+ spinal cord lesions, extending <3 vertebral segments, and a T1-Gd+ lesion in both optic nerves, near their confluence in the chiasm. After administering rituximab, there were no new relapses, with the consequent improvement of the clinical and MRI lesions. Conclusion . The concurrent display of bilateral optic neuritis and short myelitis constitutes a "borderline" case. Rituximab may represent the most appropriate therapeutic choice possible cases of NMOSD.